2016
DOI: 10.1021/jacs.6b04226
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Steady-State Ionic Concentration Profiles Formed in Electrolytes during Li-Ion Battery Operation and Determination of Mass-Transport Properties by in Situ Magnetic Resonance Imaging

Abstract: Accurate modeling of Li-ion batteries performance, particularly during the transient conditions experienced in automotive applications, requires knowledge of electrolyte transport properties (ionic conductivity κ, salt diffusivity D, and lithium ion transference number t(+)) over a wide range of salt concentrations and temperatures. While specific conductivity data can be easily obtained with modern computerized instrumentation, this is not the case for D and t(+). A combination of NMR and MRI techniques was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 36 publications
3
125
1
Order By: Relevance
“…Magnetic resonance (MR) techniques have been developed to measure several different cell properties 413 . A fundamental limitation that is difficult to overcome under typical operating conditions is that conductors are not transparent to rf irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance (MR) techniques have been developed to measure several different cell properties 413 . A fundamental limitation that is difficult to overcome under typical operating conditions is that conductors are not transparent to rf irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the cell casing is made of conductive material, such as polymer-lined aluminum in pouch or laminate cells, but also the electrodes preclude the use of conventional MR for realistic or commercial-type cell geometries. Nonetheless, MR has provided important insights into electrolyte behavior, Li-dendrite growth, and other electrochemical effects by the use of custom-built cells, which allow convenient rf access 413 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar cylindrical setups were tested by other groups before 37,38 . Such vertically standing battery housings were used for slice selective probing of a LIB in the stray field of a permanent magnet 39,40 and in combination with an additional coil for pulsed field gradients 31,32,41 . Moreover, three-dimensional 1 H MRI was applied to investigate the Li microstructure growth indirectly 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of a graphite anode and LIB separator to an in situ cell, as well as refreshment of the electrolyte following the solid-electrolyte interphase (SEI) formation cycle, would allow one to avoid the issues associated with metallic Li. It has been demonstrated that in contrast to a symmetric cell with two Li electrodes, where continuous changes in the concentration gradient occur, a steady-state (time-invariant) condition can be achieved during the operation of Li versus a graphite cell [5]. This state occurs when the diffusion flux against the formed concentration gradient compensates for the migration flux of the ions, which can be described by the following equation:…”
Section: In Situ Mrimentioning
confidence: 99%
“…The optimization of existing battery materials (cathodes, anodes, electrolytes) and development of alternative chemistries with superior properties rely heavily on characterization techniques that are capable of accurately detecting and quantifying the mechanisms of cell failure, including the identities of short-lived chemical species, and changes as functions of material properties, cycling rates, cell temperatures, and lifetimes. Nuclear magnetic resonance (NMR) spectroscopy is a method that has attracted significant attention over the past decade based on its ability to study a range of phenomena in operating energy storage devices in situ [3][4][5][6][7]. The main benefits of this technique over alternative approaches stem from its non-destructive nature and applicability to both crystalline and amorphous .…”
Section: Introductionmentioning
confidence: 99%